31 Effect of PCSK9 inhibitors on clinical outcomes and patient empowerment: a single-centre experience. (16th October 2019) - Buckley, A; O'Connor, C; Cahill, C; Khullar, N; Arockiam, S; Ahern, C; McDermott, B; Arnous, S; Kiernan, T
Abstract : Background: Atherosclerotic cardiovascular disease is significantly attributed to elevated low-density lipoprotein (LDL). Statins have been shown to reduce major adverse cardiovascular events (MACE) but their role can be limited due to intolerance. Proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors are monoclonal antibodies that prevent LDL receptor degradation, reducing circulating LDL. FOURIER and ODYSSEY have shown reductions in MACE with PCSK9 inhibitors, however, real-world data is limited due to their cost and recent introduction. Furthermore, there has been no data regarding patient-reported experience and impact of PCSK9 inhibitors on patient empowerment. Purpose: Review the impact of PCSK9 inhibitors on outcomes and patient empowerment. Methods: Retrospective cohort analysis was conducted on all patients treated locally with PCSK9 inhibitors. Data was collected by chart review. Risk classification as per ESC guidelines. MACE comprised death, MI, stent thrombosis and target vessel revascularisation (TVR). Patient empowerment was assessed using the PLACE questionnaire, derived from the Patient Enablement Instrument (figure 1 ). Question domains include positivity, negativity, motivation and well-being. Responses were compared to a control group of patients taking statin therapy. Standard Bayesian statistics were employed. Results: 24 patients were prescribed PCSK9 inhibitors since 2015. 1 patient discontinued due to flu-like symptoms and 23 patients (11 women) remain on treatment. Mean age 58.8 years (range 38–71). Median duration of treatment is 2.5 years. 2 have familial hypercholesterolaemia and 21(91.3%) have statin intolerance. 8(34.7%) for primary prevention and 15(62.5%) for secondary prevention. 13 were prescribed Alirocumab 75 mg, 5 Alirocumab 150 mg and 5 Evolocumab 140 mg. Results are summarised in table 1 . There were significant reductions in: Total cholesterol (7.3 to 4.1 mmol/L) and LDL (5.1 to 2.0 mmol/L). There was no significant change in HDL or triglycerides. 11(47.8%) were very high risk, 9(39.1%) high risk and 3(13%) moderate risk. 15(65.2%) reached target LDL. 4(17.3%) use concomitant statins. 2(8.6%) had mild flu-like symptoms and 1(4.3%) had mild injection site reactions. MACE rate was 4.3% at follow-up with 1 TVR (in the setting of poor compliance). Empowerment questionnaire indicated higher rates of Positivity, Motivation and Well-being in the PCSK9 group compared to control and negativity rates were lower. All showed statistical significance (<0.05). Discussion: Patients prescribed PCSK9 inhibitors had significant reductions in total and LDL cholesterol and low MACE at follow-up. Concomitant statin use, where possible, is important. This cohort demonstrated statistically higher self-reported positivity, motivation and well-being compared to a statin control group. Patient empowerment is an essential tool when promoting good lifestyle choices and involving patients in their own healthcare plan. Empowerment is encouraged through education and setting realistic health goals.